Large-scale environments of binary AGB stars probed by Herschel: I. Morphology statistics and case studies of R Aquarii and W Aquilae - Mayer, A.; Jorissen, A.; Kerschbaum, F.; Ottensamer, R.; Nowotny, W.; Cox, N. L. J.; Aringer, B.; Blommaert, J. a. D. L.; Decin, L.; Eck, S. van; Gail, Hans-Peter; Groenewegen, M. a. T.; et al. (Astronomy and astrophysics, 2013)
The Mass loss of Evolved StarS (MESS) sample offers a selection of 78 asymptotic giant branch (AGB) stars and red supergiants (RSGs) observed with the PACS photometer on-board Herschel at 70 μm and 160 μm. For most of these objects, the dusty AGB wind is not spherically symmetric and the wind shape can be subdivided into four classes. In the present paper we concentrate on the influence of a companion on the morphology of the stellar wind. Literature was searched to find binaries in the MESS sample, which were subsequently linked to their wind-morphology class to assert that the binaries are not distributed equally among the classes. In the second part of the paper we concentrate on the circumstellar environment of the two prominent objects R Aqr and W Aql. Each shows a characteristic signature of a companion interaction with the stellar wind. For the symbiotic star R Aqr, PACS revealed two perfectly opposing arms that in part reflect the previously observed ring-shaped nebula in the optical. However, from the far-IR there is evidence that the emitting region is elliptical rather than circular. The outline of the wind of W Aql seems to follow a large Archimedean spiral formed by the orbit of the companion but also shows strong indications of an interaction with the interstellar medium. We investigated the nature of the companion of W Aql and found that the magnitude of the orbital period supports the size of the spiral outline.